A Critique and Survey on Hasan Murtazawi’s Persian Translation of The Routledge History of Philosophy: Vol. 4 - Seyed Mustafa Shahraeini (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The present paper aims to introduce, criticize, and survey the Persian translation of  the 4th volume of The Routledge History of Philosophy: The Renaissance and Seventeenth-century Rationalism, translated by Hasan Murtazawi. The ten volumes Routledge History of Philosophy provides a chronological survey of the history of Western philosophy, from its beginnings in the sixth century BC to the present time. It discusses all the major philosophical developments in-depth. The philosophy discussed in this volume covers a period of three hundred and fifty years, from the middle of the fourteenth century to the early years of the eighteenth century: The birth of modern philosophy. The chief topics are Renaissance philosophy and seventeenth-century rationalism—in particular Descartes, Spinoza and Leibniz. This volume has been published 1993 by Routledge and translated into Persian and published in 2014 in Iran. The author aims to introduce these ten volumes,  history in general, and the 4th one in particular to Persian readers. Then, the content and form of Persian translation has been reviewed and criticized.